(untitled) (LACCEI, 2024)
Given the absence of hydrometeorological records in the Jequetepeque basin, the present study aims to generate the daily flow rates in the main channel of the river up to the Yonan station based on the gridded data of ERA5 and the French model of precipitation-runoff GR4j. This work will serve to be able to evaluate, using hydraulic models, the overflow of the Jequetepeque river and to be able to calculate the flows of maximum avenues. For this work, it is planned to carry out a calibration, validation and extension of the hydrometric records on a daily basis between the years 1979-2020.